Epistemologi Pendidikan Profetik dalam Islam: Kontribusi terhadap Pengembangan Teori Pendidikan Karakter - Mohammad Rudiyanto; Sofyan Anif (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research examines the epistemology of prophetic education in Islam and its contribution to the development of character education theory. Prophetic education, rooted in revelation, reason, and intuition (qalb), offers a holistic approach that includes intellectual, spiritual, and moral dimensions in the learning process. The main objective of this research is to identify the principles of prophetic education, such as tawhid, risalah, and morals, and analyse their influence on learners' character building. This research uses a qualitative approach with a literature review method, which involves analysing literature from classical and contemporary sources. The research findings show that prophetic education can enrich character education theory by integrating Islamic values, such as tawhid and morals, in the formation of learners' morality. In addition, prophetic education also provides an alternative to Western character education theories that tend to focus more on cognitive aspects. The implication of this research is the importance of applying the principles of prophetic education in the development of character education curriculum in Islamic educational institutions. Further research is expected to explore more deeply the application of the concept of prophetic education in various contexts of global education, especially in creating a generation that is not only knowledgeable, but also has strong character and integrity